Optimalisasi Pembelajaran Digital: Pelatihan Implementasi Kahoot! bagi Guru SDIT Annawawi Metro - M Agus Salim; Triyaningsih Triyaningsih (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to evaluate the effectiveness of training on the use of technology in learning, with a special focus on the use of the Kahoot! platform to improve teachers' knowledge, attitudes, and motivation at SDIT Annawawi Metro. The training was held for three days, from December 5 to 7, 2024, at the SDIT Annawawi Metro Hall and was attended by 26 teachers and the principal. The research method used was a quantitative approach with a pre-post questionnaire design. Pre-training and post-training questionnaires measuring knowledge, attitudes, and motivation towards the use of technology in learning were distributed before and after the training. The data collected were analyzed using descriptive statistics and t-tests for paired samples. The results showed a significant increase in all measured variables. The mean score on the post-training questionnaire increased significantly compared to the pre-training questionnaire, indicating that the training was successful in improving teachers' competence and confidence in integrating technology in learning. Statistical analysis revealed a significant difference (p <0.05), which supports the hypothesis that learning technology training improves teachers' knowledge and positive attitudes towards the use of technology in learning. The conclusion of this study shows that the use of technology, especially Kahoot!, effectively improves the quality of learning and can be further integrated into learning programs in schools. Recommendations for further studies include the implementation of similar training in various educational contexts and long-term evaluation of its impact on teaching practices.